SISTEM INFORMASI TOKO ONLINE EMOLA PARFUM - , M IRIYANTO P; , Muhammad Fakhrurrifqi, S.kom, M.Cs. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Emola perfume online shop information system is necessary to facilitate promotion process, selling, and ordering management. This is because of competition in perfume business and emola perfume online shop process management still use microsoft excel for recorded the transaction. The data placement is still untidy and placed in different folder, so that cause frequently data loss and difficult to find out profit in certain time. Emola perfume online shop information system was built based on web. This system use PHP program language with framework Code Igniter and MySQL for manage database. This system can be use to manage data such as item data, order data, and user data. Emola perfume online shop information system also has a report maker feature such as profit report in certain period and product report that most widely purchased by consumers in certain period.